2020
DOI: 10.5817/cp2020-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying sexting: Adolescent sexting and its associations with parenting styles and sense of parental social control in Israel

Abstract: Dolev -Cohen, M., & Ricon, T. (2020). Demystifying sexting: Adolescent sexting and its associations with parenting styles and sense of parental social control in Israel. AbstractThe present study examined sexting habits (sending text messages, as well as nude or semi-nude photos, and/or requesting the same from others) among adolescents, as reported by 458 students (101 boys, 357 girls), with the aim of investigating whether and how sexting correlates with parenting styles and manifestations of parental social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 78 publications
8
17
0
3
Order By: Relevance
“…The estimated rate of asking another person to send a nude photo in the Dolev-Cohen and Ricon [40] study (95% CI: 9.5%, 15.6%) is also consistent with our pooled estimate (95% CI: 9.4%, 14.6%), despite our measure also including video content. Our estimate does not coincide with that obtained by Dolev-Cohen and Ricon [40] when the person requested to send a nude photo is an established partner (95% CI: 3.7%, 7.9%), but is relatively close (95% CI: 9.2%, 15.5%).…”
Section: Evidence Of Concurrent Validitysupporting
confidence: 85%
See 3 more Smart Citations
“…The estimated rate of asking another person to send a nude photo in the Dolev-Cohen and Ricon [40] study (95% CI: 9.5%, 15.6%) is also consistent with our pooled estimate (95% CI: 9.4%, 14.6%), despite our measure also including video content. Our estimate does not coincide with that obtained by Dolev-Cohen and Ricon [40] when the person requested to send a nude photo is an established partner (95% CI: 3.7%, 7.9%), but is relatively close (95% CI: 9.2%, 15.5%).…”
Section: Evidence Of Concurrent Validitysupporting
confidence: 85%
“…Our estimate is slightly higher when the addressee is an established partner (95% CI: 13.5%, 29.2%), but the intervals are close (95% CI: 32.4%, 41.8%). This is similarly the case in comparison with Dolev-Cohen and Ricon's [40] estimate regarding the same addressee, experience, and content (95% CI: 12.3%, 18.9%). The estimated rate of asking another person to send a nude photo in the Dolev-Cohen and Ricon [40] study (95% CI: 9.5%, 15.6%) is also consistent with our pooled estimate (95% CI: 9.4%, 14.6%), despite our measure also including video content.…”
Section: Evidence Of Concurrent Validitysupporting
confidence: 73%
See 2 more Smart Citations
“…The research results showed that male respondents were more active regardless of the sexting type and motive. These findings are supported by other researches proving that boys are more involved in sexting, requesting photos from girls, importing such photos, as well as collecting and trading them (RINGROSE et al 2012;HOLLA 2017;DOLEV-COHEN & RICON 2020). Girls, on the other hand, became resigned and passive (HOLLA 2017).…”
Section: Discussionsupporting
confidence: 68%